The Printed Book of Hours of Thielman Kerver: Exploring Printer, Shop, Community and Book. - Majeski, Anna. (Tufts Archival Research Center, 2014)
Abstract: In this thesis, I have looked to two bodies of literature to reconstruct the identity of Kerver’s books of hours: scholarship on early print and on the Parisian printers, and scholarship on books of hours and their function. I have sought to bring these two together in my thesis, to gain a better and more complete picture of how Kerver’s printed books of hours functioned in context. My first two chapters address the scholarship on early print, and the characteristics used to evaluate the relationship between early print and manuscript. In a series of lectures delivered in 1960 and later published in a volume entitled, The Fifteenth Century Book: the scribes, the printers, the decorators, Curt Bühler first suggested that profound connections existed between early print and manuscript.11 Sandra Hindman, in an essay published in, Pen to Press: Illustrated Manuscripts and Printed Books in the First Century of Printing, expands on this narrative by exploring the incunabula’s fruitful experimentations with a mixture of print and hand-painted elements in illustration.12 Hindman suggests that early print and manuscript had fundamental similarities, of iconography, of illustration materials, and of format.13 These early studies frame my work on Kerver’s books of hours. They provided the grounds for an analysis of Kerver’s works which does not isolate his print production, but rather seeks to better understand Kerver’s printed hours by looking at their connections to manuscript production.